Africa's gene revolution : genetically modified crops and the future of African agriculture - Schnurr, Matthew A. (McGill-Queen's University Press, 2019)
"As development donors invest hundreds of millions of dollars into improved crops designed to alleviate poverty and hunger, Africa has emerged as the final frontier in the global debate over agricultural biotechnology. The first data-driven assessment of the ecological, social, and political factors that shape our understanding of genetic modification, Africa's Gene Revolution surveys twenty years of efforts to use genomics-based breeding to enhance yields and livelihoods for African farmers. Matthew Schnurr considers the full range of biotechnologies currently in commercial use and those in development -- including hybrids, marker-assisted breeding, tissue culture, and genetic engineering. Drawing on interviews with biotechnology experts alongside research conducted with more than two hundred farmers across eastern, western, and southern Africa, Schnurr reveals a profound incongruity between the optimistic rhetoric that accompanies genetic modified technology and the realities of the smallholder farmers who are its intended beneficiaries. Through the lens of political ecology, this book demonstrates that the current emphasis on improved seeds discounts the geographic, social, ecological, and economic contexts in which the producers of these crops operate. Bringing the voices of farmers to the foreground of this polarizing debate, Africa's Gene Revolution contends that meaningful change will come from a reconfiguration not only of the plant's genome, but of the entire agricultural system."--